Molecular bioindicators prospection from maize rhizosphere microbiota to N2O gas mitigation under stover coverage - Yoshiura, Caio Augusto (2018)
The corn crop is one of the most important crop in the world and several studies for production and yield increment have been done, but there is a lack of information about inputs combinations and interactions among microorganisms and plant roots over greenhouse gases (GHGs) emissions. Therefore, the understanding of the effects and prospect these microorganisms\' activities can provide applicable knowledge in return, producing bioproducts to improve agriculture managements. All information about microbes and their way of life are essential to looking for certain groups of microorganisms through molecular techniques like gas chromatography, quantitative PCR (qPCR), next-generation sequencing (NGS), and isolate them by classical microbiology techniques. Thus, this thesis was defined to cover a complete work from evaluate inputs used in corn crop and prospecting microbial bioindicators until isolation methods for N2O mitigation that could be applied in new commercial bioproducts in the future. Therefore, the objective purposed was to evaluate urea topdressing fertilization, microbial inoculant and maize stover interactions with rhizosphere communities in Brazilian tropical soil under controlled conditions experiments, in order to identify bioindicators for nitrous oxide (N2O) mitigation. In continuity, a lignocellulose-rich soil (Amazonian Dark Earth - ADE) was selected for comparative analysis with corn field soils (CFS) to understand maize stover degradation process and its GHGs fluxes relations; and, finally, to perform microbial isolation methods in modified media under hypoxic condition. The results revealed two or more inputs in combination can merge individual characteristics of each or potentialize their effects. The two-variable microbial inoculant and maize stover coverage combination (IS) showed as the best cost-benefit for plant biomass production (at least 10.8% more than other two- and single-variable treatments) and GHGs mitigation (12.1% less emissions than all-amendments combination treatment - i.e. FIS - which retain similar biomass production) due to interactions at rhizosphere level that revealed increment in Actinobacteria (21% to 37%) and Firmicutes (2% to 10%) phyla representativeness in comparison to other treatments. The effects derived from cellulose degradation were observed from metatranscriptome analysis that revealed an avoidance of N2O production (up to 3-fold of expression) by other pathways activities from both soils (ADE and CFS) with more intense gene expression response in ADE soils. In consequence, culture media modified for isolation of denitrifiers successfully obtained most of strains belonging to Actinobacteria and Firmicutes phyla as Bacillus, Paenibacillus, Arthrobacter and Streptomyces. In conclusion, Actinobacteria and Firmicutes showed as bioindicators for GHGs mitigation under maize stover coverage